SEAWEED: FOR FOOD, MEDICINE AND INDUSTRY - Indy, Jeane Rimber; Yasui, Hajime; Arias Rodríguez, Lenin; Álvarez González, Carlos Alfonso; Contreras Sánchez, Wilfrido Miguel (Kuxulkab’, 2014)
Seaweeds are marine macro-algae found growing throughout the world oceans and seas and none is found to be poisonous. Most of them are green (about 1,200 species), brown (about 1,750 species) or red (about 6,000 species), and most are attached by holdfasts, which have just an anchorage function, although a particularly efficient one. Why seaweed? People do not have a very good impression of seaweeds. They think that seaweeds are just some stinking, slimy nuisance that are washed up on clean sandy beaches. Most people do not realize how important seaweeds are, both ecologically and commercially. In fact, seaweeds are crucial primary producers in oceanic food webs. They are rich both in minerals and essential trace elements, also valuable sources of food, micronutrients, and raw materials for the pharmaceutical industry.